Tanggung Jawab Pelaku Usaha Terhadap Kelebihan Berat Angkut Pada Angkutan Semen Padang PT. Dunia Usaha Kota Dumai - Derma, Robby; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Law Number 22 Year 2009 on Traffic and Road Transport (LLAJ), is the legal basis that it is not allowed to withdraw levies of overload. So there needs to be the responsibility of business actors to the excess weight of transport on cement transport Padang PT. Business World Dumai City, which became one of the problems that have a major impact on the smooth flow of traffic. Therefore, the purpose of writing this thesis, namely: First, how the implementation of the responsibility of business actors on the transport of goods that are overloaded hauling, Secondly, What is the legal consequences for the transporting business that transports more than the weight of transport, Third, how the efforts of the government in to curb business actors who exceed the weight of freight.This type of research can be classified in the type of sociological legal research that is the study of the effectiveness of the current law. In this case the authors do research on the implementation in the transportation of goods by land. This research was conducted in Dumai City. Populations and samples are Business actors who use cargo trucks as a means of land transportation, Trucking entrepreneurs use cargo trucks in Dumai City as freight services, and drivers as truckers carrying truckloads that exceed the capacity of cargo.The conclusion that can be obtained from the results of the research is Firstly, the implementation of the responsibility of the business actors on the transportation of goods that are overweight of transport has not been suitable as a whole. Secondly, the legal consequences for the transporting business that transports more than the weight of the transporter should be imposed administrative sanctions and sanctions but the legal consequences have not been implemented properly. Third, the efforts of the government to curb business actors that exceed the weight of freight, namely: loading the responsibility of controlling the load of goods, the Government conducts studies on the load for the transport and Improvement of surveillance on land transportation.Keywords: Responsibility of Business Actor-Heavy Excess Heavy-Transport Dumai City